A Coaching-Based Training for Underrepresented Mentors in STEM - Molly E. Tuck; Kaylee A. Palomino; Julie A. Bradley; Margaret Mohr-Schroeder; Luke H. Bradley (Education Sciences)
As an approach, coaching-based models have been demonstrated to enhance student self-efficacy, improve grades, and increase retention and graduation rates. Coaching-based training models are also key in mentor development, focusing on open-ended questions and active listening to create supportive environments where mentees can independently find solutions. This approach not only builds mentors’ communication and leadership skills but also enhances their adaptability and problem-solving abilities. For underrepresented groups in STEM, such training positions mentors as knowledge facilitators, helping bridge gaps in mentorship experiences and bolstering confidence in their roles, thereby contributing to a more inclusive and effective learning ecosystem. This study investigates the impact of a coaching-based approach to near-peer mentor training within the UK START program, focusing on high school student participants. Interviews revealed significant benefits, including enhanced communication skills, particularly in asking open-ended questions and avoiding judgmental language. Mentors also reported improved composure in stressful situations, often utilizing techniques such as deep breathing to manage emotions during interactions with young campers. Additionally, participants experienced personal growth, seeing themselves as leaders and role models, which they attributed to the mentorship training. The role affirmed their confidence in their STEM knowledge and sparked interest in future mentorship roles. These findings suggest that structured coaching-based training can build a supportive environment, benefiting both mentors and mentees.